Evaluating food safety management systems in Singapore: A controlled interrupted time-series analysis of foodborne disease outbreak reports. (November 2020) - Aik, Joel; Turner, Robin M.; Kirk, Martyn D.; Heywood, Anita E.; Newall, Anthony T.
Abstract: Food catering service establishments are often implicated in foodborne disease outbreaks. We evaluated the effects of implementing Food Safety Management Systems (FSMS) in food catering service establishments in Singapore on two outcome measures: foodborne disease outbreaks and food hygiene violations. Using a controlled interrupted time-series study design, we estimated the change in the average level of these outcome measures following implementation, and compared the pre- and post-intervention trends. There were 42 foodborne disease outbreaks and 521 food hygiene violations associated with catering service establishments from 2012 to 2018. Eighteen months after FSMS implementation, we observed a 78.4% decrease (IRR: 0.216, 95% CI: 0.050 to 0.940, p=0.041) in the average level of foodborne outbreaks in food catering service establishments. There was no significant effect on reported hygiene violations. Our study suggests that the FSMS implementation was successful in reducing foodborne outbreaks. Highlights: Food safety management systems (FSMS) were mandated in Singapore in June 2014. Catering service linked foodborne outbreaks reduced significantly 18 months later. Food hygiene violations did not change after FSMS implementation.